Dual lysine and N‐terminal acetyltransferases reveal the complexity underpinning protein acetylation. Issue 7 (7th July 2020) - Bienvenut, Willy V; Brünje, Annika; Boyer, Jean‐Baptiste; Mühlenbeck, Jens S; Bernal, Gautier; Lassowskat, Ines; Dian, Cyril; Linster, Eric; Dinh, Trinh V; Koskela, Minna M; Jung, Vincent; Seidel, Julian; et al.
Abstract: Protein acetylation is a highly frequent protein modification. However, comparatively little is known about its enzymatic machinery. N‐α‐acetylation (NTA) and ε‐lysine acetylation (KA) are known to be catalyzed by distinct families of enzymes (NATs and KATs, respectively), although the possibility that the same GCN5‐related N ‐acetyltransferase (GNAT) can perform both functions has been debated. Here, we discovered a new family of plastid‐localized GNATs, which possess a dual specificity. All characterized GNAT family members display a number of unique features. Quantitative mass spectrometry analyses revealed that these enzymes exhibit both distinct KA and relaxed NTA specificities. Furthermore, inactivation of GNAT2 leads to significant NTA or KA decreases of several plastid proteins, while proteins of other compartments were unaffected. The data indicate that these enzymes have specific protein targets and likely display partly redundant selectivity, increasing the robustness of the acetylation process in vivo . In summary, this study revealed a new layer of complexity in the machinery controlling this prevalent modification and suggests that other eukaryotic GNATs may also possess these previously underappreciated broader enzymatic activities. Synopsis: A novel protein acetyltransferase family localized or associated to plant plastids is identified and characterised. These GCN5‐related N ‐acetyltransferases (GNATs) have unique amino acid sequence characteristics and unambiguously possess dual N ‐α‐ and ε‐lysine acetylation activities. An in silico search for putative plastidial N‐terminal and lysine acetyltransferases reveals 10 putative GNAT candidates, showing unique features both at the level of the conserved motifs and key residues. Localization to chloroplasts is confirmed for seven of them, while another one is either associated to chloroplasts or localized within the nucleus. All plastid‐associated GNATs display distinct lysine acetyltransferase and relaxed N‐ terminal acetyltransferase substrate specificities. Inactivation of GNAT2, the plastid GNAT involved in photosynthetic state transitions, results in NTA decreases confined to chloroplast proteins, next to the known decreases on photosynthetic KA target proteins. Abstract : A novel protein acetyltransferase family localized or associated to plant plastids is identified and characterised. These GCN5‐related N ‐acetyltransferases (GNATs) have unique amino acid sequence characteristics and unambiguously possess dual N ‐α‐ and ε‐lysine acetylation activities.